To evaluate the minimum number of renal scans required to follow pediatric patient postpyeloplasty - Verma, Shashwat; Saxena, Payal; Singh, Sanjeet; Khandpur, Sukhanshi; Deswal, Satyawati; Kumar, Narvesh; Singh, Anjana (World Journal of Nuclear Medicine, 2020)
The aim of the study is to evaluate the minimum number of renal scans required to follow pediatric patients postpyeloplasty. We prospectively reviewed the renal scans of 145 children with unilateral pelvi-ureteric junction obstruction who underwent dismembered pyeloplasty. Patients were then divided into four groups based on preoperative split renal function. All patients were followed with renal scan and ultrasound for minimum of 4 years. Renal scan and ultrasound were done after stent removal at 3, 6, and 12 months and then yearly after surgery. Drainage pattern (T1/2) was seen in all groups, except in patients where there was no comment on drainage pattern. Statistical analysis was performed using the Friedman ANOVA and Wilcoxon signed-ranks test as a post hoc test with Bonferroni correction and Kruskal–Wallis test with Mann–Whitney U-test as a post hoc test with Bonferroni correction. On comparison of the pattern of drainage with time in Groups 1–4, it was found that there was no significant difference with time in Group 1. Then, further, using Wilcoxon signed-rank test as post hoc test for Friedman ANOVA, Group 2 showed statistically significant difference in drainage pattern in scans between 6 months and 1 year, Group 3 showed statistically significant difference in drainage pattern in scans between 3 months and 1 year, and Group 4 showed statistically significant difference in drainage pattern in scans done between 3 and 6 months (P < 0.05). Minimum of three renal scans were required for paediatric patients post pyeloplasty at 3 months, 6 months and 1 year in the follow up period.
Keywords: Drainage; pelvi-ureteric junction obstruction; pyeloplasty; renal scan